An austral anuran assemblage in the Neotropics: seasonal occurrence correlated with photoperiod - Both, Camila; Kaefer, Igor L.; Santos, Tiago G. [UNESP]; Cechin, Sonia T. Z. (Taylor & Francis Ltd, 2008)
The study describes habitat use and temporal occurrence of calling males for an austral anuran assemblage in the Neotropics, southern Brazil. Three study sites (S1 - a permanent river and a stream, S2 - a dam and backwater, S3 - two permanent ponds periodically connected) were sampled between August 2005 and July 2006. The site S3 presented the richest and most diverse assemblage and habitat use within studied sites, and was partitioned by species groups. Richness and abundance of calling males for overall assemblage were seasonal, concentrated in spring and summer and correlated with photoperiod. Temperature, rainfall and air humidity were not correlated with the richness and abundance of calling males. Photoperiod also explained the calling seasons when species were analyzed individually. Habitat use and temporal occurrence were complementary in the partitioning of breeding resources, explaining species coexistence.
Keywords: anura; assemblages; habitat use; seasonality; Neotropics